Tafsir Qur’an Kontemporer: Pernbacaan Awal terhadap Ensiklopedi Al-Quran M. Dawam Rahardjo - Hady, M. Samsul (el Harakah: Jurnal Budaya Islam, 2005)
The theoretical construction about Alquran mufassir’s formal prerequirement almost always appears to give the absolute right for explaining God’s ‘kalam’ (ayah) to only the professional mufassir; although it should be learnt for all people especially Moslem. This is indeed an ironic since, in fact, in every period, there found one or more books/works which try to comprehend – if it cannot be called explaining – Alquran. In reality, the authors of those books did not have the so-called ‘legal certification’ to do it. M. Dawam Rahardjo, the courageous Economist, then appeared in the period when people weirdly look upon others who are lack of Arabic skills (exactly in Alquran). He tried to propose an alternative about Alquran interpretation (tafsir) which is different, or even deviate, from the theoretical construction and likely can be helpful for Moslem’s thoughts. Konstruk teoretik mengenai persyaratan formal seorang mufassir Alquran misalnya, hampir-hampir membawa kesan bahwa hanya mufassir ulung yang berhak dan dapat menjelaskan makna kalam suci Tuhan, sebuah ajaran yang sebenarnya diperuntukkan bagi manusia pada umumnya. Itu sebenarnya adalah ironi karena pada kenyataannya pada setiap penggalan zaman tetap saja muncul satu atau lebih karya yang mencoba memahami – kalau tidak dapat disebut sebagai menafsirkan – Alquran. Penulisnya, nyatanya, tidak menyandang ‘sertifikat halal’ untuk menafsirkan Alquran. M. Dawam Rahardjo, seorang ekonom yang pemberani, muncul dalam kubangan zaman yang masih memandang aneh terhadap seorang yang kurang menguasai Bahasa Arab-nya Alquran mencoba menawarkan satu alternative tafsir Alquran yang berbeda atau menyimpang dari konstruk teoretik dan – mungkin – terkesan membantu dalam pemikiran muslim.